Literature and religion : a dialogue between China and the West. - Jasper, David (The Lutterworth Press, 2022)
How does one culture 'read' another? In Literature and Religion, two scholars, one from China and one from the West, each read texts from the other's culture as a means of dialogue. A key issue in such an enterprise is the nature of religion and what we understand by that term in a world in which ancient religious customs seem to be dying or under threat. Does a comparative study of religious literature offer a way towards mutual understanding - or merely illustrate our differences? Underpinned by their own friendship, these two partners in conversation show what is possible.